The Eye in Pediatric Systemic Disease - Levin, Alex V.; Enzenauer, Robert W.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book is the first of its kind to describe ocular manifestations of systemic diseases in the pediatric population. Written and edited by experts in areas of pediatric ophthalmology and genetics, this new text covers a multitude of topics in a comprehensive and cataloged fashion. The Eye in Pediatric Systemic Disease is designed as an in-depth and up-to-date reference work that is heavily referenced, thus allowing the reader ready access to the international supporting literature. Everything from ocular manifestations of hematologic disease, child abuse, psychiatric diseases, renal disorders, and vitamin disorders are covered, allowing readers to know what to look for in the eyes of children with a given systemic disorder. The Eye in Pediatric Systemic Disease is written in language that is accessible to ophthalmologists and pediatricians, as well as allied health care professionals.
1. Normal Postnatal Ocular Development -- 2. Ocular Manifestations of Prematurity -- 3. Ocular Manifestations of Allergic and Immunologic Diseases -- 4. Ocular Manifestations of Cardiac Disease -- 5. Ocular Manifestations of Child Abuse -- 6. Oculofacial Manifestations of Chromosomal Aberrations -- 7. Ocular Manifestations of Craniofacial Disorders -- 8. Ocular Manifestations of Dermatologic Diseases -- 9. Ocular Manifestations of Endocrinologic Diseases -- 10. Ocular Manifestations of gastrointestinal disease -- 11. Hematologic Disorders of the Eye -- 12. Ocular Manifestations of Infectious Diseases -- 13. Ocular Manifestations of Inborn Errors of Metabolism -- 14. Ocular Manifestations of Musculoskeletal Disorders -- 15. Ocular Manifestations of Neurologic Diseases -- 16. Phakomatoses-Neurocutaneous Syndromes -- 17. Ocular Manifestations of Psychiatric Diseases -- 18. Ocular Manifestations of Pediatric Pulmonary Diseases -- 19. Ocular Manifestations of Pediatric Renal Diseases -- 20. Ocular Manifestations of Pediatric Rheumatic Diseases -- 21. Ocular Manifestations of Systemic Syndromes -- 22. Ocular Manifestations of Vitamin Disorders.
Keywords: Medicine; Ophthalmology; Pediatrics; Medicine & Public Health; Ophthalmology; Pediatrics